Pengaruh Pendidikan Gizi Seimbang Dengan Media Audio Visual Terhadap Pengetahuan Siswa Sd Negeri Pajang Iii Surakarta - SHOLIKAH WIDIYANTI, AMALIA, Luluk Ria Rakhma, S.Gz., M.Gizi, Muwakhidah, SKM, M.Kes (2015)
Background: : Nutrition illumination is one way of nutrition education, nutrition ilumination is an educative approach to produce individual behavior to improve the better of nutrition. Objective : To determine the effect of balance nutrition education with audio visual media to the student's knowledge of SD Negeri Pajang III Surakarta. Research Method: The method used in this study is quasy experimental study with one group pretest-posttest design. The population in this study were students in grade 3 and 4 in SD Negeri Pajang III Surakarta. With a number of 75 people. The sampling technique used in making sample in this research is by simple random sampling. Number of samples in this study were 45 students. Result: : The results showed that before given nutrition education, the average level of knowledge was 56.55 + SD 15.29 while after being given the nutrition education, level of the knowledge was 74.33 + SD 18.69. Through Paired sample T-test was obtained p = 0.000 where p <0.05 so that Ho is rejected. An average increase of the knowledge was 17.78. Conclusion: There is a difference of knowledge about balanced nutrition before and after the given nutrition education using audio visual media on elementary school students in SD Negeri Pajang III Surakarta Keywords: : nutrition education, nutrition knowledge, balance nutrition, audio visual Bibliography: 23 :1991-2014